Efektivitas Program E-Parking dalam Pelayanan Publik di Taman Bungkul Surabaya - Theodora Thessa Renata Putri; Sri Umiyati; Budi Rianto (Public Administration Dept, Faculty of Social and Political Science, 2022)
This research aims to reduce the practice of illegal parking attendants and the leakage of parking retribution income can be overcome. The problem is focused on assessing the effectiveness of e-parking in Tama Bungkul Surabaya with reference to the theory of effectiveness according to Budiani (2007). The data obtained through interviews, observation, and documentation and analyzed qualitatively. This study concludes that the implementation of e-parking in Bungkul Park has not been effective because it has not yet been targeted, as evidenced by the finding of people who are less interested in paying for parking through e-parking machines, program socialization has been carried out directly and through social media, parking objectives have been achieved because they have there are no illegal parking practices and leakage of parking fees, while for program monitoring, periodic e-parking machines are checked, but four e-parking machines are found in the Bungkul Park area that cannot be used and have not been repaired until now due to the lack of reliable human resources